Pengaruh Model Pembelajaran Sole (Self Organized Learning Environment) terhadap Kemampuan Menulis Teks Eksposisi di Kelas VIII SMP Pahlawan Nasional Kota Medan - Surip, M.; br Kaban, Rahel Yena (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research is a final assignment research (Thesis) and was conducted at the Medan City National Hero Middle School in class VIII with 2 classes and a total of 20 students in each class. Data in research using questionnaires and tests. Questionnaires containing questions will be distributed to class VIII students individually and submitted to researchers. Next, during the class VIII students' test, the researcher asked them to create an opinion or new idea that they knew about in the expository text material. Because, researchers looked at the process of writing ability of class VIII students in expository text material. The results of research that has been carried out on class VIII students show that: (1) To analyze students' ability to write exposition texts in Indonesian language subjects using a direct learning model from class VIII of National Hero Middle School. With a score of 66.42 vulnerable in this learning, students still have not mastered and are able to use the learning model that has been given by the facilitator (teacher) (2) To analyze how students are able to write expository texts in Indonesian language subjects using the Self-Organized learning model Learning Environment. With a maximum score of 84.85, it can be seen that it is very different from the learning model used by the teacher in that class. Therefore, researchers suggest that the SOLE model can attract students in the learning process. (3) To analyze whether there is an influence on the Self-Organized Learning Environment learning model on the writing ability of class VIII students of Medan National Hero Middle School.